Efecto de la cocción en la disminución de anti nutrientes de hojas de zanahoria blanca (Arracacia xanthorrhiza) y camote (Ipomoea batatas) - Yungán Acalo, Edith Viviana (2024)
The objective of this work was to evaluate the effect of cooking on the content of antinutrients (saponins, tannins, alkaloids, oxalates, glucosinolates and nitrates) and functional compounds (carotenoids, phenols and antioxidants) in leaves of four white carrot genotypes (ECU -18969, ECU-18949, ECU-1206, ECU-18932) and four sweet potato genotypes (Pedrito, Buena Vista, Guayaco M, Toquecita) in raw and cooked states, the analyzes were determined applying methodologies from different authors, which were adapted to laboratory conditions. The results obtained were analyzed using DCA with a 2x4 factorial arrangement and statistical differences were determined using Tukey (p<0.05). In antinutrient content in white carrot leaves, the ECU 18969 variety presented a lower concentration for alkaloids and saponins (1.14 mg/100g and 2.22 mg/100g) and in sweet potato leaves, the Toquecita variety presented a lower concentration of alkaloids and saponins. and tannins (4.21 mg/100g; 1.09 mg/100g and 3.29 g/100g). The application of cooking in white carrot and sweet potato leaves reduces the content of antinutrients and functional compounds, with statistically significant differences between raw and cooked states, where the antinutrients that were reduced in the highest percentage were tannins with a reduction of up to 93% and 94% in white carrot and sweet potato leaves respectively.